Generation Z in Workplace Human Capital Development Strategy: Case Study of Private Employee Skills Gen-Z Category - Firman Karim; A. Ifyani Haanurat; Andi Mappatompo (www.amertainstitute.com, 2025)
The entry of Generation Z into the workforce brings new challenges for organizations, especially in managing human capital development strategies. The generation that grew up in the digital era has unique characteristics, such as high-tech skills, a need for recognition, and a preference for flexibility and collaboration. However, many private companies still use conventional approaches to human capital development, which are potentially irrelevant to Gen Z's expectations. This study aims to explore the perceptions of Gen Z private sector employees towards human capital development strategies implemented in the workplace. Using a descriptive qualitative approach, data was collected through observations, interviews, and questionnaires with Gen Z employees. The expected result is an in-depth understanding of Gen Z's experiences, expectations, and assessments of HR development programs, as well as the formulation of more adaptive and effective strategies. The findings are expected to be the basis of recommendations for companies in creating an inclusive work environment and supporting the productivity of the younger generation in a sustainable manner.